Magic breaks ebook - Andrews, Ilona (Kate Daniels, 2014)
No matter how much the paranormal politics of Atlanta change, one thing always remains the same in this #1 New York Times bestselling series: if there’s trouble, Kate Daniels will be in the middle of it… As the mate of the Beast Lord, Curran, former mercenary Kate Daniels has more responsibilities than it seems possible to juggle. Not only is she still struggling to keep her investigative business afloat, but she must now deal with the affairs of the Pack, including preparing her people for attack from Roland, a cruel, ancient being with godlike powers. As Roland’s long shadow looms ever nearer, Kate is called to attend a gathering of leaders from Atlanta’s supernatural factions. When one of the Masters of the Dead is found murdered by a shapeshifter, Kate is given less than twenty-four hours to hunt down the killer. And this time, if she fails, she’ll find herself embroiled in a war that could destroy everything she holds dear...